The Influence of Learning Models and Learning Styles on Students' Science Literacy in Primary School - Abdul Azis Nasution; Retno Dwi Suyanti; Wildansyah Lubis (Randwick International of Education and Linguistics Science Journal, 2023)
The purposes of this research are to analyze: 1) The influence of learning models on students' science literacy abilities, 2) The influence of learning styles on students' science literacy abilities, and 3) The interaction between learning models and types of learning styles on students' science literacy abilities in primary school. This type of research is a Quasi-Experimental design with Nonequivalent Pretest-Posttest Control Group Design. In this study, The population was all fifth-grade students of SD Negeri 067251 Medan Deli. With sampling techniques and totaling samples, the entire population was sampled. Research instruments in the form of learning style questionnaires and science literacy assesment. The data were analyzed using Two-Way Anova with the help of IBM's SPSS version 26 program. The results showed that: 1) There is an influence of learning models on students' science literacy abilities (sig. 0.00 < 0.05); 2) There is an influence of student learning styles on students' science literacy abilities (sig. 0.014 < 0.05); and 3) There is an interaction between learning models and learning styles on students' science literacy abilities in primary schools (sig. 0.043 < 0.05).